Development of SSIBL e-modules on ecology and biodiversity materials to improve critical thinking and motivation - Anggi Kusumasari; Evi Suryawati; Lenny Anwar (Universitas Muhammadiyah Malang, 2024)
The development of SSIBL-based E-modules is motivated by the importance of critical thinking skills and learning motivation in science learning that must be possessed by students. It was found that the limited teaching materials used as well as critical thinking skills and student learning motivation were still in the low category in science learning. This study aims to test the effectiveness and feasibility of SSIBL-based E-modules on ecology and biodiversity material for Indonesian junior high school students, especially at SMPN 23 Pekanbaru. The type of research used is development research with the ADDIE method. The results of the validation of the SSIBL-based E-module assessment by material experts obtained an average score of 3.72 with a very feasible category. The results of the assessment validation by pedagogical experts amounted to 3.97 with a very feasible category. The results of the assessment validation by media experts amounted to 3.95 with a very feasible category. The effectiveness of the E-module with the MANOVA test obtained a sig value of 0.000. This means that there are differences in critical thinking skills and learning motivation between the experimental class using the SSIBL-based E-module and the control class that does not use the SSIBL-based E-module. Based on the results of this SSIBL-based E-module research, it is recommended that it can be used to improve students' critical thinking skills and learning motivation.